2010
DOI: 10.1308/003588410x12771863936648
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative inspiratory muscle training preserves postoperative inspiratory muscle strength following major abdominal surgery – a randomised pilot study

Abstract: Pre-operative specific IMT improves MIP pre-operatively and preserves it postoperatively. Further studies are required to establish if this is associated with reduced pulmonary complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
2
8

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(109 citation statements)
references
References 23 publications
5
94
2
8
Order By: Relevance
“…4,17,31 Preoperative breathing exercises may be useful in this high-risk population, although prior studies have shown mixed results. 6,19,32 Our data are consistent with much of the literature regarding the use of postoperative IS for prevention of PPCs. Lowrisk patients have shown mixed benefit of IS following abdominal or cardiac surgery in terms of recovery of pulmonary function, prevention of PPC, or reduction in length of hospital stay.…”
Section: Discussionsupporting
confidence: 88%
“…4,17,31 Preoperative breathing exercises may be useful in this high-risk population, although prior studies have shown mixed results. 6,19,32 Our data are consistent with much of the literature regarding the use of postoperative IS for prevention of PPCs. Lowrisk patients have shown mixed benefit of IS following abdominal or cardiac surgery in terms of recovery of pulmonary function, prevention of PPC, or reduction in length of hospital stay.…”
Section: Discussionsupporting
confidence: 88%
“…Preoperative inspiratory muscle strength training (IMST) has been shown to reduce the incidence of postoperative respiratory complications in high-risk cardiac surgery patients [14] and has also been demonstrated to preserve postoperative inspiratory muscle strength following major abdominal surgery [15]. …”
Section: Introductionmentioning
confidence: 99%
“…According to Smetana, preoperative IMT appears to be an important strategy in the prevention of PPC and has been used by some authors in thoracic, cardiac and abdominal surgeries 2,4,9,10. However, there are no studies that evaluate the effect of preoperative IMT in obese patients undergoing open bariatric surgery, and only one study has reported the effects of postoperative IMT 11…”
Section: Introductionmentioning
confidence: 99%